PENGARUH INDEPEDENSI, KOMPETENSI DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT ( Study Pada Kantor Akuntan Publik di Bandar Lampung ) - Sari, Pipit Novila; Balkis, Puteri Sophia (LPPM UNIVERSITAS BINA INSAN, 2019)
This research aims to analyze the influence of independence, competence, and professionalism of auditor toward the audit quality at public accountant office in di Bandar Lampung. The number of the auditorswho are being the sample of this research are 40 auditors from 2 Public Accounting Office in Bandar Lampung. This research employs a sampling collection technique by using saturation sampling method with all members from the population used as the sample. The questionnaire filling is using the Likertscale.The data analysis methods which are employed is multiple linear regressionanddetermination coefficient analysiswhich are processed by SPSS for windows 20. The hypothesis test is tested through F testandt test. The result of this research shows that independence, competenceand professionalismof an auditor, both for the simultaneous and partial, influence positively toward the audit quality.